COMPARATIVE LINGUISTICS: UNVEILING THE INTRICACIES OF LANGUAGE EVOLUTION AND DIVERSITY - Mamirova Shahnoza Qahramon qizi; Zilola Abduraxmonova (TADQIQOTLAR.UZ, 2023)
Abstract: This article delves into the field of comparative linguistics, a discipline that explores the similarities and differences among languages to unravel the secrets of language evolution and diversity. Comparative linguistics plays a vital role in understanding how languages evolve, how they are related, and how they shape human communication and culture. By examining various linguistic features, such as phonetics, grammar, and vocabulary, researchers can construct language family trees and trace the historical connections between different languages. This article provides an overview of the key concepts and methodologies employed in comparative linguistics and highlights its significance in unraveling the mysteries of human language.